N-type liquid crystal elastomer-based ion thermoelectric fiber and preparation method and application thereof
By using a combination of liquid crystal elastomer and ionic liquid, high-performance, durable N-type liquid crystal elastomer-based ionic thermoelectric fibers are prepared, which solves the problems of insufficient tensileability and cyclic durability of existing ionic thermoelectric materials, and realizes lightweight, low-dimensionality and high-performance fiber preparation.
Patent Information
- Application Number
- CN202411814522.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-04-08
AI Technical Summary
At this stage, ionic thermoelectric materials are mainly P-type materials, lacking N-type materials, and the stretchability and cyclic durability of the materials are limited by the interaction between the material substrate and ions, which cannot meet the needs of real-life applications.
Using liquid crystal elastomer as the substrate, N-type liquid crystal elastomer-based ionic thermoelectric fibers were prepared through soaking ionic liquids, which improved the Seebeck coefficient, stretchability and cyclic durability of the fibers.
It has achieved the preparation of high-performance, durable stretchable N-type thermoelectric fibers, and has the characteristics of lightweight, low-dimensionality, and cyclic durability, which has promoted the research and application of N-type thermoelectric materials.
Smart Images

Figure CN119789764A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of thermoelectric materials, and particularly relates to an N-type liquid crystal elastomer-based ionic thermoelectric fiber and a preparation method and application thereof. Background Art
[0002] As the energy crisis intensifies, waste heat from nature, industry and human body is considered to be an important resource that has been neglected and wasted. Among new energy technologies, thermoelectric technology has received widespread attention because it can directly convert thermal energy into electrical energy, and is considered to be one of the effective ways to solve the energy crisis. Compared with traditional thermoelectric materials, such as PbTe, Si / G and Bi2Te3, emerging ionic thermoelectric materials have attracted extensive research in recent years due to their advantages such as higher Seebeck coefficient, simple preparation process and green environmental protection.
[0003] At present, most of the research on ionic thermoelectric materials based on plastic materials such as PEO, PVDF-HFP, PVA, and cellulose is mainly based on P-type materials, most of which are in the form of thin films and blocks, and the stretchability and cycle durability of the materials are limited by the interaction between the material substrate and ions (Tian Li, Xin Zhang, Steven D. Lacey, et al. Nature materials, 2019, 18: 608-613, Wei Zhao, Tingting Sun, Yiwei Zheng, et al. Advanced Science, 9, 2201075). Due to the lack of N-type materials, the singleness of the form, and the constraints between thermoelectric performance and stretchability and cycle durability, ionic thermoelectric materials cannot meet the needs of practical applications. Therefore, the development of a low-dimensional, stretchable, durable, high-performance N-type ionic thermoelectric material is of great significance to the development of thermoelectric and wearable fields. Summary of the invention
[0004] In view of the existing technical problems, the technical problem to be solved by the present invention is to provide an N-type liquid crystal elastomer-based ionic thermoelectric fiber and its preparation method and application. The deficiency of the current lack of research on ionic thermoelectric N-type materials is overcome, and the Seebeck coefficient, stretchability and cycle durability of the N-type ionic thermoelectric fiber are greatly improved.
[0005] The invention provides a liquid crystal elastomer-based ionic thermoelectric fiber, which comprises a fiber substrate and a thermoelectrically active material; wherein the fiber substrate material is a liquid crystal elastomer, and the thermoelectrically active material is an ionic liquid.
[0006] Furthermore, the liquid crystal elastomer-based ionic thermoelectric fiber uses liquid crystal elastomer as a substrate and ionic liquid as an immersion solution, and the N-type ionic thermoelectric fiber is obtained by immersion in the solution at room temperature.
[0007] The present invention provides a method for preparing a liquid crystal elastomer-based ionic thermoelectric fiber, comprising:
[0008] (1) 2-methyl-1,4-phenylenebis(4-((6-(acryloyloxy)hexyl)oxy)benzoate), 2,2'-(ethylenedioxy)diethylmercaptan, pentaerythritol tetrakis-3-mercaptopropionate, 2,6-di-tert-butyl-4-methylphenol, tripropylene glycol diacrylate, and a solvent are mixed and stirred;
[0009] (2) adding triethylamine to step (1), stirring to obtain a liquid crystal elastomer solution, then injecting the liquid crystal elastomer solution into a mold, standing to form, and obtaining a liquid crystal elastomer fiber;
[0010] (3) The liquid crystal elastomer fiber is immersed in an ionic liquid solution to obtain a liquid crystal elastomer-based ionic thermoelectric fiber.
[0011] Preferably, in step (1), the molar ratio of 2-methyl-1,4-phenylenebis(4-((6-(acryloyloxy)hexyl)oxy)benzoate), 2,2'-(ethylenedioxy)diethylmercaptan and pentaerythritol tetrakis-3-mercaptopropionate is 1:1-3:0.1-0.5, and the molar ratio of 2,6-di-tert-butyl-4-methylphenol and tripropylene glycol diacrylate is 1:0.1-0.3.
[0012] The solvent in step (1) is N,N-dimethylformamide.
[0013] Preferably, the stirring in step (1) is performed at 70-80° C. for 20-30 min.
[0014] Preferably, in step (2), the volume ratio of triethylamine to N,N-dimethylformamide is 20-30:1.
[0015] Preferably, the stirring time after adding triethylamine in step (2) is 0.5-2 min.
[0016] Preferably, the mold in step (2) is a tubular mold; and the standing still is horizontal standing still for 10-15 hours.
[0017] The mold comprises a polytetrafluoroethylene tube or one of various glass material molds.
[0018] In the step (2), a syringe is used to inject into the mold.
[0019] In the step (2), the liquid crystal elastic fiber is obtained by leaving the formed fiber to stand for a while and then peeling it off.
[0020] Preferably, the ionic liquid in step (3) is one or more of 1-butyl-3-methylimidazolium acetate, 1-butyl-3-methylimidazolium dicyanamide, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-allyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium acetate, lithium tetrafluoroborate, 1-ethyl-3-methylimidazolium dicyanamide, and 1-butyl-3-methylimidazolium hexafluorophosphate.
[0021] Preferably, the solvent containing the ionic liquid solution in step (3) is ethyl acetate;
[0022] The concentration of the ionic liquid solution in step (3) is 0.5 to 0.95 mol / L;
[0023] The immersion time in step (3) is 1 to 12 hours.
[0024] The present invention provides an application of the liquid crystal elastomer-based ionic thermoelectric fiber in the fields of ionic thermoelectricity and intelligent wearables.
[0025] The present invention uses liquid crystal elastomer as the substrate of ionic thermoelectric material, and successfully prepares a high-performance N-type liquid crystal elastomer-based ionic thermoelectric fiber with good cycle durability by soaking in ionic liquid solution. Figure 1 As shown, the network structure of the liquid crystal elastomer is composed of highly polymerized liquid crystal molecular chains, in which the coordination effect between cations and molecular chains not only limits their thermal diffusion behavior under the action of temperature difference, but also expands the difference in the migration rate of anions and cations. This method can not only make the liquid crystal elastomer fiber have ultra-high N-type thermoelectric properties, but also have excellent durability and mechanical properties.
[0026] The ionic thermoelectric fiber of the present invention uses liquid crystal elastomer as a substrate, and ionic liquid acts as a thermoelectrically active donor. A high-performance, durable and stretchable N-type ionic thermoelectric fiber is prepared by a mold method and an impregnation method. The present invention achieves the preparation of durable N-type ionic thermoelectric fibers with ultra-high Seebeck coefficient and mechanical properties based on liquid crystal elastomer by regulating the synthesis parameters of the liquid crystal elastomer, the type of ionic liquid impregnation, and the interaction between ions and elastomer molecular chains, and optimizing the impregnation time and concentration, solving the current lack of research on high-performance N-type ionic thermoelectric materials. The obtained ionic hotspot fibers have the characteristics of light weight, low dimensionality, stretchability, and cyclic durability, which promotes the research on N-type ionic thermoelectric materials and has great application potential.
[0027] Beneficial Effects
[0028] (1) The present invention provides a simple and practical method for preparing N-type liquid crystal elastomer-based ionic thermoelectric fibers. The method is simple to operate, has a short preparation cycle, and has stable effects, and is convenient for large-scale production.
[0029] (2) Compared with other ionic thermoelectric materials, the present invention uses liquid crystal elastomer as the ionic thermoelectric material substrate, and through the immersion of ionic liquid solution, the anions, cations and liquid crystal elastomer molecular chains interact with each other. When the immersion time reaches 1 to 12 hours, the preparation of N-type liquid crystal elastomer ionic thermoelectric fiber can be achieved. Compared with an ionic thermoelectric gel disclosed in patent CN118459789A and an ionic thermoelectric film disclosed in patent CN114447203A, the materials disclosed in the above patents are only P-type thermoelectric materials, and the preparation process is complicated and the cyclic tensile performance is poor. In contrast, the preparation process of the N-type liquid crystal elastomer-based ionic thermoelectric fiber of the present invention is simple, and it has excellent mechanical properties and cyclic tensile performance stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is the mechanism diagram of N-type liquid crystal elastomer-based ionic thermoelectric fiber;
[0031] Figure 2 This is a graph of the Seebeck coefficient of the N-type liquid crystal elastomer ionic thermoelectric fiber at different immersion times in Example 1;
[0032] Figure 3 is the stress-strain curve of the liquid crystal elastomer-based ionic thermoelectric fiber in Example 2;
[0033] Figure 4 It is the change rate of Seebeck coefficient of the liquid crystal elastomer-based ionic thermoelectric fiber in Example 2 after cyclic stretching.
[0034] Figure 5 This is a comparison chart of the Seebeck coefficients of the N-type liquid crystal elastomer ionic thermoelectric fiber in Example 1 among thermoelectric fibers at the current stage. DETAILED DESCRIPTION
[0035] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0036] The main reagents used in the embodiments of the present invention are as follows: lithium tetrafluoroborate provided by Shanghai Yuanye Biotechnology Co., Ltd., liquid crystal elastomer synthesis raw materials 2-methyl-1,4-phenylene bis(4-((6-(acryloyloxy)hexyl)oxy)benzoate) and 2,2'-(ethylenedioxy)diethyl mercaptan provided by Shanghai Bid Pharmaceutical Technology Co., Ltd., pentaerythritol tetrakis-3-mercaptopropionate and tripropylene glycol diacrylate provided by Shanghai Titan Technology Co., Ltd., 2,6-di-tert-butyl-4-methylphenol provided by Shanghai Aladdin Biochemical Technology Co., Ltd., and triethylamine provided by Shanghai Myrel Biochemical Technology Co., Ltd., all without any other treatment.
[0037] Seebeck coefficient S i is based on the slope method, according to S i = -ΔV / ΔT The formula was measured using a self-built device, where the potential difference ΔV was generated by 8 temperature differences ΔT recorded by Keithley 2182A. Each sample was tested 3 times and the average value was taken. The linear correlation between ΔV and ΔT (R 2 ) should be greater than 0.99. The stress-strain curve was tested on an Instron (5969) tester at a speed of 50 mm / min at room temperature.
[0038] Example 1
[0039] (1) 2.63 g of 2-methyl-1,4-phenylenebis(4-((6-(acryloyloxy)hexyl)oxy)benzoate), 0.85 g of 2,2'-(ethylenedioxy)diethanethiol, 0.25 g of pentaerythritol tetrakis-3-mercaptopropionate, 0.02 g of 2,6-di-tert-butyl-4-methylphenol and 0.4 g of tripropylene glycol diacrylate were dissolved in 2 ml of N,N-dimethylformamide, and the mixture was stirred at 75° C. for 20 min. Then, 100 μL of triethylamine was added and stirred for 1 min to obtain the product;
[0040] (2) injecting the product obtained in step (1) into a polytetrafluoroethylene tube through a syringe, leaving it to stand for 10 to 15 hours to form, and peeling it off to obtain liquid crystal elastomer fibers;
[0041] (3) dissolving lithium tetrafluoroborate in 5 mL of ethyl acetate and stirring for 30 min to obtain an ionic liquid soaking solution, wherein the concentration of lithium tetrafluoroborate in the ionic liquid solution is 0.5 mol / L;
[0042] (4) The liquid crystal elastomer fiber formed in step (2) is immersed in the solution prepared in step (3) for 6 hours to obtain an N-type liquid crystal elastomer ionic thermoelectric fiber.
[0043] The Seebeck coefficient of the N-type liquid crystal elastomer ionic thermoelectric fiber prepared in this embodiment after being immersed in 0.5M lithium tetrafluoroborate solution for 6 hours was -27.4mV K by the Seebeck test system. -1 .
[0044] The variation of the Seebeck coefficient of the N-type liquid crystal elastomer ionic thermoelectric fiber prepared in this embodiment with the soaking time of the ionic liquid is tested, and the results are as follows: Figure 2 As shown in Figure 2, when the immersion time is 6 hours, the measured Seebeck coefficient of the N-type liquid crystal elastomer ionic thermoelectric fiber is the highest. It can be seen that the fiber reaches adsorption saturation after immersion for 6 hours. The generation of this ultra-high Seebeck coefficient is also due to the liquid crystal molecular chain and Li + The coordination effect of the anion and cation leads to an increase in the difference in migration rates, as shown in the mechanism Figure 1 shown.
[0045] Example 2
[0046] (1) 2.63 g of 2-methyl-1,4-phenylenebis(4-((6-(acryloyloxy)hexyl)oxy)benzoate), 0.85 g of 2,2'-(ethylenedioxy)diethanethiol, 0.25 g of pentaerythritol tetrakis-3-mercaptopropionate, 0.02 g of 2,6-di-tert-butyl-4-methylphenol and 0.4 g of tripropylene glycol diacrylate were dissolved in 2 ml of N,N-dimethylformamide, and the mixture was stirred at 75° C. for 20 min. Then, 100 μL of triethylamine was added and stirred for 1 min to obtain the product;
[0047] (2) injecting the product obtained in step (1) into a polytetrafluoroethylene tube through a syringe, leaving it to stand for 10 to 15 hours to form, and peeling it off to obtain liquid crystal elastomer fibers;
[0048] (3) dissolving lithium tetrafluoroborate in 5 mL of ethyl acetate and stirring for 30 min to obtain an ionic liquid soaking solution; wherein the concentration of lithium tetrafluoroborate in the ionic liquid solution is 0.6 mol / L.
[0049] (4) The liquid crystal elastomer fiber formed in step (2) is immersed in the solution prepared in step (3) for 6 hours to obtain an N-type liquid crystal elastomer ionic thermoelectric fiber.
[0050] The Seebeck coefficients of the N-type liquid crystal elastomer ionic thermoelectric fibers prepared in this embodiment after being immersed in 0.6M lithium tetrafluoroborate solution for 6 hours were -24.1 mV K -1 .
[0051] The mechanical properties of the N-type liquid crystal elastomer-based ionic thermoelectric fiber prepared in this embodiment were tested, and the results are as follows: Figure 3 As shown in the figure, the maximum strain after 6 hours of immersion is 284.7% and the maximum stress is 583.6KPa. Figure 4 As shown, after 500 cycles of stretching using a small flexibility testing instrument, the change rate of the Seebeck coefficient is less than 5%, which has good practicality.
Claims
1. A liquid crystal elastomer-based ionic thermoelectric fiber, characterized in that: The thermoelectric fiber comprises a fiber substrate and a thermoelectrically active material; The fiber base material is a liquid crystal elastomer, and the thermoelectric active material is an ionic liquid.
2. A method for preparing a liquid crystal elastomer-based ionic thermoelectric fiber, comprising: (1) 2-methyl-1,4-phenylenebis(4-((6-(acryloyloxy)hexyl)oxy)benzoate), 2,2'-(ethylenedioxy)diethylmercaptan, pentaerythritol tetrakis-3-mercaptopropionate, 2,6-di-tert-butyl-4-methylphenol, tripropylene glycol diacrylate, and a solvent are mixed and stirred; (2) adding triethylamine to step (1), stirring to obtain a liquid crystal elastomer solution, then injecting the liquid crystal elastomer solution into a mold, standing to form, and obtaining a liquid crystal elastomer fiber; (3) The liquid crystal elastomer fiber is immersed in an ionic liquid solution to obtain a liquid crystal elastomer-based ionic thermoelectric fiber.
3. The preparation method according to claim 2, characterized in that: In the step (1), the molar ratio of 2-methyl-1,4-phenylenebis(4-((6-(acryloyloxy)hexyl)oxy)benzoate), 2,2'-(ethylenedioxy)diethylmercaptan and pentaerythritol tetrakis-3-mercaptopropionate is 1:1-3:0.1-0.5, and the molar ratio of 2,6-di-tert-butyl-4-methylphenol and tripropylene glycol diacrylate is 1:0.1-0.3; and the solvent in the step (1) is N,N-dimethylformamide.
4. The preparation method according to claim 2, characterized in that: The stirring in step (1) is performed at 70-80° C. for 20-30 min.
5. The preparation method according to claim 2, characterized in that: The volume ratio of triethylamine to solvent in the step (2) is 20-30:
1.
6. The preparation method according to claim 2, characterized in that: The stirring time in step (2) is 0.5-2 min.
7. The preparation method according to claim 2, characterized in that: In the step (2), the mold is a tubular mold; and the standing still is horizontal standing still for 10-15 hours.
8. The preparation method according to claim 2, characterized in that: In the step (3), the ionic liquid is one or more of 1-butyl-3-methylimidazolium acetate, 1-butyl-3-methylimidazolium dicyanamide, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-allyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium acetate, lithium tetrafluoroborate, 1-ethyl-3-methylimidazolium dicyanamide, and 1-butyl-3-methylimidazolium hexafluorophosphate.
9. The preparation method according to claim 2, characterized in that: The solvent of the ionic liquid solution in step (3) is ethyl acetate; the concentration of the ionic liquid solution is 0.5 to 0.95 mol / L; and the immersion time is 1 to 12 hours.
10. An application of the liquid crystal elastomer-based ionic thermoelectric fiber according to claim 1 in the fields of ionic thermoelectricity and smart wearables.
Citation Information
Patent Citations
Giant thermoelectric potential ion thermoelectric film and preparation method thereof
CN114447203A
Preparation method of stretchable dual-network ion thermoelectric hydrogel
CN118459789A